STUDY THE KINETIC OF NEW PHOTO-STABILIZER (4-STEAROYLRESORCINOL) PRODUCTION USING BATCH REACTOR - Alfaize, Dr. M.M.; Niema, Dr. S.A.; Alhamar, G.J. (Basrah Journal for Engineering Sciences, 2014)
4-Stearoylresorcinol was prepared by acylation of resorcinol with stearoyl chloride in the presence of zinc chloride as catalyst in a batch reactor. The temperature range of reaction was (50-80)°C. The rate of acylation increased with temperature up to (70°C). The conversion of reactants appeared to follow second order kinetic model. The reaction rate constant was (0.0031 1/mol.min) and was higher at higher temperatures. Activation energy was (16.8258 kJ/mol). The optimal catalyst concentration was (2.9936 mol/l). Also, a quantitative relationship was derived to represent the weight of the product as a function to the reaction variables. The quantitative relationship gave mean deviation equal to (5%). The product concentration was measured by UV spectroscopy.